Potency of stored DNA derived from buccal mucosal epithelial cells for genotype analysis of interleukin 4 -590 C/T - Rezmelia Sari; Alya Nur Fadhilah; Prayitno Prayitno (Faculty of Dentistry, Universitas Gadjah Mada, 2019)
The genotype variation of the interleukin 4 (IL-4) gene on spot -590 C/T is known to correlate with IL-4 protein expression in periodontitis, but the results found in the population are inconsistent. Sequencial genotype analysis of multiple genes often used stored DNA samples obtained from buccal mucosal epithelial cells. This study aims to determine the use of stored DNA samples obtained from buccal mucosal epithelial cells for genotype analysis specifically on -590 C/T IL-4 genes. This is a descriptive analytical study. The samples were 58 DNA derived from the buccal mucosal epithelial cells taken by sterile cotton swab isolated with PrestoTM kit (GeneAid). The DNA has been stored for 2 years at -20 °C. The genotype analysis was conducted using PCR RFLP technique with BSmFI enzyme and the data were presented descriptively. The results show that 51.72% of the stored DNA is still in good condition and 37.9% can be used for genotype analysis. It was concluded that DNA derived from buccal mucosal epithelial cells stored at -20 °C for 2 years can still be used for genotype analysis, but the quality of DNA is affected by storage time.